Transnational Models of Citizen Participation: The Case of Participatory Budgeting - Sintomer, Yves (2012)
Tis article pursues two main objectives. First, it provides a transnational overview and analysis of participatory budgeting, which has been central to the literature on democratic innovations in citizen participation. Second, it combines this broad empirical project with a theoretical approach based on the construction of ideal-types in the Weberian tradition. Namely, it presents six models of citizen participation: participatory democracy, proximity democracy, participative modernization, multi-stakeholder participation, neo-corporatism, and community development. Although these models have evolved from participatory budgeting and the European context, it is our contention that they can help us to understand the sociopolitical and ideological dynamics, contexts and impacts of civic engagement and democracy today at the transnational scale.